Regulating humanity's impact on the earth: The promise of transnational environmental law. Issue 5 (5th December 2022) - Webster, Emily
Abstract: Transnational environmental law (TEL) is a relatively new field of research that is agitated by the concept of the Anthropocene. Like environmental law, TEL suffers from certain methodological challenges which are exacerbated by the sheer ammount of activity involved in the generation of transnational legal norms and regulation. This article argues that, despite some of these challenges, TEL is well placed to evolve further to better regulate human activity in the Anthropocene. It argues that to better reflect on what the Anthropocene means for TEL and how it may develop in practice, it must engage further with power, the problem of erasure of weaker actors, and the legacies of colonialism on the one hand, and the sciences – particularly Earth system science and ecology ‐ on the other. By doing so it would offer a more robust analysis of TEL and insights into its further development in practice.